2018
DOI: 10.4103/ejim.ejim_37_18
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of serum irisin level in thyroid disorder

Abstract: BackgroundIrisin is a newly discovered myokin secreted by myocytes responsible for transmission of signals from muscles to other body tissues. Irisin improves systemic metabolism by increasing the energy expenditure. Owing to numerous similarities in action between irisin and thyroid hormones it seems imperative to explore these substances' potential mutual influence on the body. Objective To estimate serum irisin concentration in patients with hypothyroid and hyperthyroid diseases, and to detect the relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Exercise is a crucial part of the lifestyle adjustment that can help people with non-alcoholic fatty liver disease (NAFLD). Although the mechanism underlying this exercise-induced liver fat reduction was unknown, it was shown that plasma irisin levels negatively correlated with intrahepatic triglyceride levels, indicating that irisin may play a role in the pathogenesis of NAFLD (31) . Low density lipoprotein (LDL) and low high density lipoprotein (HDL) levels are markedly elevated in the atherogenic lipid profile of patients with fatty liver disease.…”
Section: Irisin and Fatty Liver Diseasementioning
confidence: 99%
“…Exercise is a crucial part of the lifestyle adjustment that can help people with non-alcoholic fatty liver disease (NAFLD). Although the mechanism underlying this exercise-induced liver fat reduction was unknown, it was shown that plasma irisin levels negatively correlated with intrahepatic triglyceride levels, indicating that irisin may play a role in the pathogenesis of NAFLD (31) . Low density lipoprotein (LDL) and low high density lipoprotein (HDL) levels are markedly elevated in the atherogenic lipid profile of patients with fatty liver disease.…”
Section: Irisin and Fatty Liver Diseasementioning
confidence: 99%